Close-up and macro photography its art and fieldcraft techniques - Thompson, Robert (Routledge, Taylor & Francis Group, 2018)
"Focusing on fieldcraft techniques for macro and close-up photography, Thompson covers the vital but often overlooked skills necessary to achieve consistent professional results in the field. Case studies covering a broad and often challenging group of subjects from the seashore to your back garden form the core of the lavishly illustrated book. Biology, life history, subject behaviour and ethics along with best practice approaches are discussed in detail and underpinned with photographic tips. The book is divided into four sections--Digital Fundamentals, Fieldcraft & Methodology, Portfolio Case Studies, Digital Workflow & Presentation--covering the full photographic process from capture through to editing, captioning, development and storage are discussed. Moving beyond the surface-level approach to macro instruction, this book provides readers with techniques that work in the field. Illustrated with over 250 of the author's own inspiring images, this publication is a must for photographers, naturalists and anyone interested in improving their macro skills in the field."--Provided by publisher
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Photography, Close-up -- Technique; Macrophotography -- Technique; Photographie en gros plan; Technique; Macrophotographie; Technique; PHOTOGRAPHY; Techniques; Digital (see also COMPUTERS; Digital Media; Photography); PHOTOGRAPHY; General